(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study aims to elucidate the attitudes of the Prophets (peace be upon them) when they experienced the loss of a child or faced delayed offspring, as reflected in the Qur’anic verses, and to examine the resulting implications of these attitudes. The research included two main topics: first: the attitudes of the prophets when children are lost and offspring are delayed. Second: the implications arising from these attitudes. The research employs an inductive and deductive methodology through tracing and analyzing the stories of the Prophets in the Qur’an. Among the key findings are that patience is one of the greatest virtues a believer can arm themselves with when facing trials and calamities, and that acceptance of God’s decree allows the believer to live in peace and reassurance. The study also highlights the importance of demonstrating need for God, adhering to supplication and acts of worship, and hastening to perform righteous deeds, as well as their effects during trials. Moreover, it emphasizes maintaining a good opinion of God and exerting efforts while warning against despair and hopelessness. The research also clarifies the harm of continuing to succumb to Satanic whispers without resistance and underscores the lessons drawn from emulating the Prophets’ responses to the loss of children, adopting them as a life approach to face all adversities and trials.